How to study biofilms: technological advancements in clinical biofilm research - Leanne Cleaver; James A. Garnett (Frontiers in Cellular and Infection Microbiology, 2023)
Biofilm formation is an important survival strategy commonly used by bacteria and fungi, which are embedded in a protective extracellular matrix of organic polymers. They are ubiquitous in nature, including humans and other animals, and they can be surface- and non-surface-associated, making them capable of growing in and on many different parts of the body. Biofilms are also complex, forming polymicrobial communities that are difficult to eradicate due to their unique growth dynamics, and clinical infections associated with biofilms are a huge burden in the healthcare setting, as they are often difficult to diagnose and to treat. Our understanding of biofilm formation and development is a fast-paced and important research focus. This review aims to describe the advancements in clinical biofilm research, including both in vitro and in vivo biofilm models, imaging techniques and techniques to analyse the biological functions of the biofilm.